The Influencer of Creator and MSMe Collaboration on Store Growth in Tiktok Shop - Putri, Anggun Rianda (Jurnal Digital Bisnis, Modal Manusia, Marketing, Entrepreneurship, Finance, & Strategi Bisnis (DImmensi), 2026)
This study examines the influence of collaboration between content creators and micro, small, and medium enterprises (MSMEs) on store growth in TikTok Shop. In the context of rapidly expanding social commerce, collaboration with creators has become an important strategy for MSMEs to increase product exposure and sales performance. This research aims to analyze how partnerships with creators contribute to the development of MSME stores on TikTok Shop. A quantitative approach was employed using survey data collected from 200 MSME owners who actively sell products through TikTok Shop. The respondents were selected using purposive sampling, focusing on MSMEs that have experience collaborating with creators. The data were analyzed using multiple regression to examine the relationship between creator–MSME collaboration and store growth. The findings indicate that collaboration with creators has a positive and significant effect on store growth. Creator partnerships enhance product visibility, consumer trust, and audience engagement, which in turn contribute to increased sales volume and follower growth of MSME stores. The results suggest that the quality and consistency of creator collaboration play an important role in strengthening the performance of MSMEs in the TikTok Shop ecosystem.This study provides practical insights for MSME owners in optimizing creator partnerships as a strategic tool to improve business growth on social commerce platforms. It also contributes to the literature on digital marketing and social commerce by highlighting the role of collaborative marketing in emerging e-commerce environments.